2015
DOI: 10.1016/j.avb.2015.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Victim, perpetrator, and offense characteristics in filicide and filicide–suicide

Abstract: The purpose of this paper is to provide a critical review of most recent studies of parental and stepparental filicide. A detailed review of the literature revealed the importance of certain demographic, environmental, and psychosocial factors in the commission of child homicide.Our findings indicate that filicides perpetrated by genetic parents and stepparents differ considerably in terms of underlying motivational factors. Data in the literature suggest that biological parents are more likely to choose metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 87 publications
3
50
0
3
Order By: Relevance
“…classification, those involving intimate partners are still the most prevalent. Consistent with prior research indicating it is rare for mothers who kill infants to commit suicide ; none of the homicide–suicides in Cuyahoga County during this 26‐year period involved mothers committing neonaticide or infanticide.…”
Section: Discussionsupporting
confidence: 85%
“…classification, those involving intimate partners are still the most prevalent. Consistent with prior research indicating it is rare for mothers who kill infants to commit suicide ; none of the homicide–suicides in Cuyahoga County during this 26‐year period involved mothers committing neonaticide or infanticide.…”
Section: Discussionsupporting
confidence: 85%
“…Overall, the diagnostic findings of our study are in line with those of several previous studies (Bourget et al, 2007;Debowska, Boduszek, & Dhingra, 2015;Flynn et al, 2007Flynn et al, , 2013Hatters Friedman, Hrouda, et al, 2005;Lysell et al, 2014;Putkonen, Amon, et al, 2009), although inter-study comparisons in this field are problematic, as discussed in the introductory chapters. To our knowledge, the presence of autism-spectrum disorders has not previously been reported in a sample of child-homicide offenders, although such disorders have been noted among the victims (Coorg & Tournay, 2012;Palermo, 2003).…”
Section: Study IVsupporting
confidence: 92%
“…Some studies have suggested a potential link between childhood trauma and filicide (Debowska et al 2015;Mugavin 2005;Oberman and Meyer 2008;Smithey 1997). For instance, Crimmins et al (1997) have approached the issue from a self-psychological perspective, suggesting that serious negative experiences during childhood cause damage to a woman's self, making it difficult for her to care for dependents.…”
Section: Research On Childhood Negative Life Events Of Filicidal Womenmentioning
confidence: 99%